2020
DOI: 10.4317/medoral.23804
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte- and platelet-rich fibrin does not provide any additional benefit for tooth extraction in head and neck cancer patients post-radiotherapy: a randomized clinical trial

Abstract: Background One of the most important complications of radiotherapy (RT) for head and neck cancer (HNC) is osteoradionecrosis (ORN) of the jaws, arising mainly from tooth extractions. Thus, the present study aimed to evaluate the efficacy of leukocyte- and platelet-rich fibrin (L-PRF) in preventing ORN following tooth extraction in post-irradiated HNC patients, as well as other postoperative complications. Material and Methods 23 patients previously submitted to conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Only studies that were published within 3 years of the search date were included ( n = 60). After duplicate removal and screening, 50 articles were included in the analysis 35‐84 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only studies that were published within 3 years of the search date were included ( n = 60). After duplicate removal and screening, 50 articles were included in the analysis 35‐84 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported no significant difference in healing following extraction in 23 previously irradiated patients with or without L-PRF protocol, although as osteoradionecrosis is a rare complication, a larger sample may have been required. 74 Another included study found that in patients diagnosed with alveolar osteitis, A-PRF significantly improved self-reported pain and later bony infill on two-dimensional imaging compared to saline irrigation. 72 Two studies reported no significant benefit with the use of PRF compared to control.…”
Section: Oral Surgery (Extractions Socket Preservation and Implant Pl...mentioning
confidence: 99%
“…Within this framework, recovery is graded on a scale from 1, indicating very poor recovery, to 5, signifying excellent recovery. 7 The analysis incorporated six studies [8][9][10][11][12][13] that utilized LTH index for assessing the surgical site wound healing of patients on the seventh day following oral carcinoma resection. These studies encompassed a total of 93 patients who received PRF treatment and 97 patients who were part of the control group.…”
Section: Evaluation Of Landry Turnbull and Howley Wound Healing Indexmentioning
confidence: 99%
“…les dents avec profondeur de sondage supérieure à 5 mm, atteinte de la furcation, lésion carieuses avec atteinte pulpaire, les dents retenues, les dents avec obturation de grande étendue ou à impact occlusal, les dents dévitalisées sans traitement canalaire ou avec un traitement défectueux constituent des dents à pronostic douteux [41] qui doivent susciter l'attention du clinicien avant radiothérapie pour indiquer ou non leur extraction selon les paramètres précités Lorsque l'état de la pathologie sous-jacente le permet, un temps de 10 à 14 jours doit être accordé lorsque les dents sont extraites avant l'irradiation [42] Les avulsions doivent être atraumatiques avec une cicatrisation muqueuse complète avant radiothérapie [11] Le protocole chirurgical consiste en une antisepsie extraorale avec 2% de chlorhexidine à base aqueuse et intraorale avec 0,2% de chlorhexidine à base aqueuse, anesthésie locale sans vasoconstricteur avec 3% de mépivacaïne, et technique chirurgicale atraumatique (syndesomotomie soigneuse, pas de divulsion et d'ostéotomie mucopériostée, luxation dentaire et avulsion avec forceps et élévateurs, vigoureux curetage et irrigation abondante des alvéoles avec une solution saline à 0,9% , la technique de suture X avec du nylon monofilament 4-0 sans tension excessive). [43] Soins Conservateurs : Commençons par signaler qu'il n'existe pas au niveau de la littérature un protocole standard de prise en charge des patients irradiés , Tolentino et Coll ont recommandé un délais de 20 jours avant radiothérapie pour les procédures non invasives et de 30 jours pour les procédures invasives [44]. Un rinçage de la bouche à l'aide d'une solution de 10 ml de gluconate de Chlorhexidine à une concentration de 0.2% 2 fois par jour est recommandé avant radiothérapie, elle permet en association avec un brossage correcte de maintenir une hygiène bucco-dentaire satisfaisante [39].Il a été aussi rapporté que Les préparations neutres de fluorure et de Chlorhexidine réduisent le risque de caries post radiques [45].…”
Section: Introductionunclassified